2014
DOI: 10.1098/rsif.2014.0169
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-decorated titanium with enhanced antibacterial activity through adhesive polydopamine for dental/bone implant

Abstract: Implant-associated infections, which are normally induced by microbial adhesion and subsequent biofilm formation, are a major cause of morbidity and mortality. Therefore, practical approaches to prevent implant-associated infections are in great demand. Inspired by adhesive proteins in mussels, here we have developed a novel antibiotic-decorated titanium (Ti) material with enhanced antibacterial activity. In this study, Ti substrate was coated by one-step pH-induced polymerization of dopamine followed by immob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 57 publications
7
92
0
Order By: Relevance
“…It has been reported that the catechol/quinone groups on PDA could crosslink with nucleophilic amine groups via a Schiff base reaction. 28,30,31 In agreement with this notion, the tentative assignment of the peak at m/z 261 is C 13 H 14 N 2 O 4 + (see the inset of Figure 2b) that results from interactions between the amine groups of PAM and the catechol groups of PDA. This reaction connects the PDA chains to the PAM networks.…”
Section: Resultssupporting
confidence: 57%
“…It has been reported that the catechol/quinone groups on PDA could crosslink with nucleophilic amine groups via a Schiff base reaction. 28,30,31 In agreement with this notion, the tentative assignment of the peak at m/z 261 is C 13 H 14 N 2 O 4 + (see the inset of Figure 2b) that results from interactions between the amine groups of PAM and the catechol groups of PDA. This reaction connects the PDA chains to the PAM networks.…”
Section: Resultssupporting
confidence: 57%
“…In the present study, the late markers of osteogenic differentiation (Alizarin Red staining) could be observed on the Ti-BC surface within 2 weeks. In contrast to other antibiotics immobilized on the dopamine coated Ti, which could be only able to enhance antibacterial activity [37]. The bacitracin modified Ti surface could not only exhibit the antibacterial properties but also promote the osteogenic differentiation, which was of great importance to prevent the orthopedic implant infection.…”
Section: Discussionmentioning
confidence: 98%
“…An interactive implant surface with pH-dependent or infection-dependent antibiotic release might avoid this shortcoming, but has not yet been introduced to dental implant materials research. Antibiotics are capable of reducing bacterial colonization with S. mutans 22,39) S. epidermidis 31) and S.aureus 38) , P. gingivalis, A. actinomycetemcomitans, P. intermedia, P. aeruginosa 40) and E. coli 21,23,36) on titanium surfaces. Chlorhexidine (CHX)-loaded titanium surfaces reduce colonization with streptococci and S. aureus in comparison to titanium control [24][25][26] .…”
Section: Drug-loaded Surfacesmentioning
confidence: 99%